2017
DOI: 10.1002/asia.201700049
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Developed Organic Salts of Tolfenamic Acid and Its β‐Alanine Derivatives for Dual Purposes as an Anti‐Inflammatory Topical Gel and Anticancer Agent

Abstract: A new series of primary ammonium monocarboxylate (PAM) salts of a nonsteroidal anti-inflammatory drug (NSAID), namely, tolfenamic acid (TA), and its β-alanine derivatives were generated. Nearly 67 % of the salts in the series showed gelling abilities with various solvents, including water (biogenic solvent) and methyl salicylate (typically used for topical gel formulations). Gels were characterized by rheology, electron microscopy, and so forth. Structure-property correlations based on single-crystal and powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 102 publications
(206 reference statements)
0
8
0
Order By: Relevance
“…It was further supported by cell migration assay carried out on the same cell line; the speed with which the cells migrated were 9.5, 2.5, and 1.75 μm h −1 for untreated, tolfenamic acid–treated, and G94 ‐treated cells, respectively. The data clearly suggested that G94 most efficiently inhibited cancer cell migration ( Figure ) …”
Section: Designing Lmwgsmentioning
confidence: 91%
See 1 more Smart Citation
“…It was further supported by cell migration assay carried out on the same cell line; the speed with which the cells migrated were 9.5, 2.5, and 1.75 μm h −1 for untreated, tolfenamic acid–treated, and G94 ‐treated cells, respectively. The data clearly suggested that G94 most efficiently inhibited cancer cell migration ( Figure ) …”
Section: Designing Lmwgsmentioning
confidence: 91%
“…a) Chemical structures G88 – G96 ; b) crystal structure illustration of gelator and nongelator salts displaying 1D HBN in G88 and 2D HBN in NG89 , G91 , G93 , and NG95 ; c) PGE 2 assay of G94 in MDA‐MB‐231 breast cancer cell line; d) migration of the cell front observed at different time intervals in scratch assays performed on MDA‐MB‐231 cells after treatment with TA and G94 (scale bar 100 μm). Reproduced with permission . Copyright 2017, Wiley‐VCH Verlag GmbH & Co. KGaA.…”
Section: Designing Lmwgsmentioning
confidence: 99%
“…[ 1 ] Recently, it has been discovered that TA can also be used as a novel anticancer therapeutic agent against different types of cancers. [ 6–10 ] It is also reported to exert bactericidal activity against H. pylori , S. aureus , B. pseudomallei , and L. asiaticus [ 11–14 ] and has shown effectiveness in slowing down the progress of Alzheimer's disease. [ 15–20 ] A comprehensive review on TA has previously been published.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15–20 ] A comprehensive review on TA has previously been published. [ 5 ] Different spectrofluorimetric methods have been developed for determination of TA in serum samples [ 21 ] , interaction of bovine serum albumin and human serum albumin (HAS) with TA [ 22 ] , and for the evaluation of anticancer and anti‐inflammatory actions of TA [ 9 ] , but none of these methods has been validated or applied to the tablet dosage form of TA.…”
Section: Introductionmentioning
confidence: 99%
“…47 A D-glucosamine-derived hydrogel was effective at treating wounds in in vivo studies. 48 We have also demonstrated that the supramolecular synthon approach is helpful in converting nonsteroidal-anti-inflammatory drugs (NSAIDs) to supramolecular gels that could be used to treat inflammation (both in vitro 49 and in vivo 50 ).…”
Section: ■ Introductionmentioning
confidence: 99%